Heating Before or After Complexation Differentially Affects Structural and Functional Properties of Whey Protein Isolate–Gallic Acid Complexes - Pangastuti, Hesti Ayuningtyas; Wattanachaisaereekul, Songsak; Karnjanapratum, Supatra; Pinsirodom, Praphan (My University, 2026)
Whey proteins readily form complexes with polyphenols, the structure and functionality of which are influenced by factors such as polyphenol concentration and heat treatment. However, previous studies have largely examined these factors independently, and limited information is available regarding how the sequence of heat application (pre- vs. post-complexation) interacts with varying polyphenol concentrations to modulate the structure–function relationship of whey protein-polyphenol systems. This study investigated the effects of different heating conditions and gallic acid (GA) concentration on structural and functional properties of whey protein isolate–gallic acid (WPI-GA) complexes at pH 7.0. The treatments included native whey protein isolate (WPI), preheated WPI, native WPI-GA complexes, and WPI-GA complexes at two ratios (1:0.5 and 1:1 w/w) and heated either before or after complexation. GA addition and heat treatment increased turbidity and particle size, indicating enhanced complexation. The zeta potential showed minimal change, suggesting limited involvement of electrostatic interactions. Fluorescence quenching increased with GA concentration, confirming interactions between GA and WPI. Heat treatments increased fluorescence intensity and surface hydrophobicity, likely due to protein unfolding and exposure of hydrophobic regions. Higher GA concentration enhanced antioxidant activity, reduced foaming capacity, and did not affect emulsifying properties. Preheating also decreased the foaming capacity of the complexes, whereas post-heating restored it. Both heat treatments reduced the emulsifying activity index (EAI) but increased the emulsion stability index (ESI) compared with native WPI. Overall, this study provides insight into how GA concentration and heating sequence influence the complexation and functionality of WPI, contributing to a better understanding of protein–polyphenol interactions in bioactive-enriched dairy systems.
Keywords: emulsifying stability; heating sequence; interfacial properties; protein–polyphenol interaction; whey protein isolate